2016
DOI: 10.1152/japplphysiol.01111.2015
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in plasma BDNF levels after prolonged bed rest

Abstract: Brain-derived neurotrophic factor (BDNF) is a member of the family of neurotrophins and has been implicated in brain resistance to insults. Murine studies have demonstrated increased hippocampal concentration after acute immobilization and decreased concentration after chronic immobilization. In humans, chronic stress and sedentary lifestyle result in decreased plasma BDNF levels, but there no data exist regarding acute immobilization. The aim of our study was to evaluate age-related responses [comparing 7 you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
1
17
0
1
Order By: Relevance
“…When we designed this and the previous study [26], we hypothesized that we would have found a decrease in BDNF in people undergoing bed rest, and that this decrease would have been less important in people undergoing cognitive training, based on data coming from literature. The results were surprising, showing exactly the opposite.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When we designed this and the previous study [26], we hypothesized that we would have found a decrease in BDNF in people undergoing bed rest, and that this decrease would have been less important in people undergoing cognitive training, based on data coming from literature. The results were surprising, showing exactly the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that bed rest induces an increase in plasma BDNF in adult/older, but not in young people [26]. Studies on animals [35] and on humans affected by diabetes and Alzheimer's disease [36, 37 ] seem to suggest a biphasic behaviour of BDNF with increased level in the first phase of disease and decreased level in a later phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma BDNF was found to be correlated with TG levels (33). In contrast, the expression of TrkB in endothelium was reduced in atherosclerotic lesions in the patients with high levels of TC, TG, LDL-C and glucose, when compared with that in the subjects with normal lipid profiles (34).…”
Section: Discussionmentioning
confidence: 93%